Narcissistic personality disorder in historical figures: the case of Bartolomé de las Casas - Ordóñez Alberca, Danny (2022)
Throughout History, there have been a number of relevant people who have influenced the version of the truth that we all think we know. Between them is the brother Bartolomé de las Casas whose alleged philanthropic view sought that the Indians from America had a better treatment on behalf of the Spaniards. However, his masked philanthropy made Bartolomé de las Casas alter the real History from both daily talks and institutionalized Education. The aim of this paper is to analyze Bartolomé de las Casas’ personality from the current Psychology`s perspective. By using the Diagnostic and Statistical Manual of Mental Disorders (DSM) and unpublished documents collected by Luis Torres in 1867 we try to show that Bartolomé de las Casas has narcissist trails and there is a fundamentalist thought in his Personality, which needs constant self-validation.